1985
DOI: 10.1002/ajpa.1330660309
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by distance, linguistic similarity, and the genetic structure on Bougainville Island

Abstract: Previous research has revealed extensive genetic variation among villages on Bougainville, in the Solomon Islands. Using previously published gene frequency data for seven loci, the role of isolation by distance in structuring genetic variation on Bougainville was reanalyzed. Newer methods of kinship estimation show that earlier estimates of the isolation by distance parameters were low. The fit of the model is highly significant (R2 = 0.409; P less than 0.001), and the parameter estimates indicate high isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…This method was preferred to Pearson's product moment correlation ''r'' since it assumes only a monotonic relationship, not a linear one, between the variables (Pollard 1977, Relethford, 1985. While Spearman's was preferred for methodological reasons, it is worth noting that values obtained from our data set with the two methods were very similar, and most of the differences were due to a slightly greater value of Spearman's coefficients (data not shown).…”
Section: Data Analysesmentioning
confidence: 89%
“…This method was preferred to Pearson's product moment correlation ''r'' since it assumes only a monotonic relationship, not a linear one, between the variables (Pollard 1977, Relethford, 1985. While Spearman's was preferred for methodological reasons, it is worth noting that values obtained from our data set with the two methods were very similar, and most of the differences were due to a slightly greater value of Spearman's coefficients (data not shown).…”
Section: Data Analysesmentioning
confidence: 89%
“…Some of these processes may be implicit in the patterns of population structure, and the R-matrix analysis, particularly the regression of mean heterozygosity/phenotypic variance on the distance of populations from the centroid (Harpending and Ward 1982;Relethford and Blangero 1990), is supposed to offer useful insights in this regard. The above proponents of the model and many other later investigators (Devor et al 1984;Relethford 1985;Jantz and Meadows 1995;Puppala and Crawford 1996;Reddy and Chopra 1999;Reddy et al 2000) found encouraging results in their application of the model to several case studies involving local populations.…”
Section: Discussionmentioning
confidence: 91%
“…Table 6 presents results for Brac that bear on genetic-linguistic-geo aphic corresponenetics and linguistics would covary ? Relethford, 1985) and 2) since geography has been shown to influence genetic structure (Jorde, 1980), both genetic distances and linguistic distances would correlate positively with geographic distance. Only the linguistics-geogra hy relationship turned correlation (r = 0.4286) is highly significant, whereas neither the genetics-linguistics (r = 0.0581) nor the genetics-geography correlation (r = -0.1732) is statistically significant (Table 6).…”
Section: G E N E T I C D I S T a N C E ( G E N E Substitutions) Dolmentioning
confidence: 94%